Older persons, political participation, and the Decade of Healthy Ageing: an international legal analysis* - Paiola, Jessyca (Revista JRG de Estudos Acadêmicos, 2024)
The increase in global population ageing, coupled with advancements in the study of active ageing, underscores the need for deeper discussions centred on older adults. Among various fundamental subjects regarding this population, participation in social and political life stands out, with the act of voting in elections serving as a significant expression of such engagement. This article seeks to explore some key sources of International Law that focus on older people, emphasizing the element of political participation. This study was developed from a qualitative, exploratory research, through a bibliographic and documental review, by gathering pertinent legislation. Initially, it examines international legal frameworks related to the subject, progressing to an analysis of the Decade of Healthy Ageing, and the 2030 Agenda for Sustainable Development. The conclusion drawn from this study is that the lack of a global treaty addressing the rights of older adults reflects the ongoing invisibility experienced by this population. Therefore, it is essential to foster discussions about older people´s political participation and to implement measures that ensure they are not only beneficiaries of services but also agents of change.